2017
DOI: 10.1016/j.healthplace.2017.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic density and risk of mental ill health – The case of religious sectarianism in Northern Ireland: A population data linkage study

Abstract: An ethnic group that lives in a neighbourhood in which it is in the minority, termed 'lower ethnic density,' tends to report a higher incidence of mental ill-health. This population-based study investigated for the first time the existence of an own-group density effect among Catholic and Protestant communities in Northern Ireland. The entire Northern Ireland born Catholic and Protestant working age (n = 1, 004,060) enumerated population in the 2011 Census of Northern Ireland were included in the study via adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
1
5
1
Order By: Relevance
“…Compared to the Protestant/other Christian group the Catholic (OR=0.91), Other Faith/Philosophy (OR=0.78), and No Faith/Philosophy (OR=0.90) groups had significantly lower risk of antidepressant prescribing. This is in contrast to the findings of O' Reilly and Stevenson (2003) who reported no significant difference between Catholics and Protestants on scores on the General Health Questionnaire, and Bosqui et al (2017) who found that selfreported poor mental health was higher for Catholics (8.69%) than Protestants (7.06%), although the effect was moderated by the own-group religious neighbourhood density. It would appear, even if there are no differences in prevalence of depression, that the Protestant/other Christian group are more likely to be in receipt of anti-depressants.…”
Section: Discussioncontrasting
confidence: 97%
“…Compared to the Protestant/other Christian group the Catholic (OR=0.91), Other Faith/Philosophy (OR=0.78), and No Faith/Philosophy (OR=0.90) groups had significantly lower risk of antidepressant prescribing. This is in contrast to the findings of O' Reilly and Stevenson (2003) who reported no significant difference between Catholics and Protestants on scores on the General Health Questionnaire, and Bosqui et al (2017) who found that selfreported poor mental health was higher for Catholics (8.69%) than Protestants (7.06%), although the effect was moderated by the own-group religious neighbourhood density. It would appear, even if there are no differences in prevalence of depression, that the Protestant/other Christian group are more likely to be in receipt of anti-depressants.…”
Section: Discussioncontrasting
confidence: 97%
“…Mental health status was also based on the responses to the Census question that asked if people had experienced ‘ an emotional, psychological or mental health condition (such as depression or schizophrenia )’ which had lasted, or was expected to last at least 12 months. This indicator has been used as a measure of mental ill-health in a range of previous studies (Tseliou et al ., 2016; Bosqui et al ., 2017; Doebler et al ., 2017; Maguire et al ., 2017; Wright et al ., 2018; Rosato et al ., 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Studies on other mental disorders, namely depression and anxiety, found a more mixed picture, but an overall protective or neutral effect for ethnic minorities in the UK or USA (Shaw et al, 2012). The mechanisms of this protective effect are not well understood, and are impeded by limited studies in different contexts and populations, different minority experiences (Bosqui et al, 2017), and on symptom clusters and severity rather than incidence (Bardol et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This serves as a natural control for broader minority effects, enabling a concentration on minority experience at the neighbourhood level. A recent Census-based study on self-reported mental health using the entire enumerated population of Northern Ireland, found no group density effect for the Protestant population, and a strong reverse effect for the Catholic population, where own-group density was harmful for mental health (Bosqui et al, 2017). This is partially supported by findings from the Northern Ireland First Episode Psychosis Study (NIFEPS), which found an increased incidence risk of a psychotic disorder for both Catholics and Protestants in higher-own group density neighbourhoods, with a 7 times greater risk for Catholics compared to a low own-group area, and 5 times for Protestants, even after adjusting for area deprivation and urbanicity (Mulholland et al, under review) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation